The role of oxidative stress and inflammation in obesity and its impact on cognitive impairments —a narrative review - Naomi, Ruth; Teoh, Soo Huat; Embong, Hashim; Balan, Santhra Segaran; Othman, Fezah; Bahari, Hasnah; Yazid, Muhammad Dain (Multidisciplinary Digital Publishing Institute, 2023)
Obesity is a chronic low-grade inflammatory condition that induces the generation of oxidative stress and inflammation. This oxidative stress and inflammation stimulate brain atrophy and some morphological changes in the brain that eventually result in cognitive impairments. However, there is no exact study that has summarized the role of oxidative stress and inflammation in obesity and its impact on cognitive impairments. Thus, the objective of this review is to recapitulate the current role of oxidative stress and inflammation in cognitive decline based on in vivo evidence. A comprehensive search was performed in Nature, Medline and Ovid, ScienceDirect, and PubMed, and the search was limited to the past 10 years of publication. From the search, we identified 27 articles to be further reviewed. The outcome of this study indicates that a greater amount of fat stored in individual adipocytes in obesity induces the formation of reactive oxygen species and inflammation. This will lead to the generation of oxidative stress, which may cause morphological changes in the brain, suppress the endogenous antioxidant system, and promote neuroinflammation and, eventually, neuronal apoptosis. This will impair the normal function of the brain and specific regions that are involved in learning, as well as memory. This shows that obesity has a strong positive correlation with cognitive impairments. Hence, this review summarizes the mechanism of oxidative stress and inflammation that induce memory loss based on animal model evidence. In conclusion, this review may serve as an insight into therapeutic development focusing on oxidative stress and inflammatory pathways to manage an obesity-induced cognitive decline in the future.